Loss imbalance effect on inter-core crosstalk in bidirectional uncoupled multi-core fiber transmission - Cartaxo, A. (Journal of Lightwave Technology, 2023)
The effect of core loss imbalance on inter-core crosstalk (XT) is studied theoretically and numerically in long-haul bidirectional uncoupled multi-core fiber transmission. The coupled power equations are solved for two cores with imbalance of loss coefficients, and the solution is used to obtain expressions for direct, indirect, backscattered and bidirectional XT powers. These expressions generalize expressions reported by other authors to arbitrary loss coefficients. It is shown that, in the range of the loss coefficient imbalance from-0.04 dB/km to 0.04 dB/km, the XT powers in decibel show approximately a linear dependence on the loss coefficient imbalance. In that range, differences of the indirect XT power of nearly 1.2 dB relative to the indirect XT power with equal loss coefficients can occur for the larger loss coefficient imbalance; for the direct and backscattered XT powers, the differences are even larger, reaching around 2 dB. These values of 1.2 and 2 dB of difference translate directly to the bidirectional XT power of long-haul 2-core fiber links, in case of dominance of indirect and backscattered XT, respectively.